UKRAINE’S ROLE IN THE FORMATION OF A NEW WORLD ECONOMIC ARCHITECTURE: A VIEW THROUGH THE PRISM OF BOHDAN HAVRYLYSHYN’S IDEAS - Shevchenko, Olena (МІЖНАРОДНА ЕКОНОМІКА В УМОВАХ КЛІМАТИЧНИХ ЗМІН: ГЛОБАЛЬНІ ВИКЛИКИ, 2026)
.